Poetyka (nie)wyrażalnego pożądania, czyli zarys historii powie- ści gejowskiej w Polsce na tle socjologiczno-kulturowym - Jackowiak, Adrianna (Studia Europaea Gnesnensia, 2014)
The aim of the paper is to show the history of Polish gay novel and explain the very term. However, the essence of the research problem is not the history itself, but drawing attention to the need of adopting a multidimensional perspective in the deliberations concerning homosexuality in general (including gay novel). An interdisciplinary approach to the issue enables one to make observations concerning the impact of social and political realities on literature, while at the same time to analyse a work of art as a statement in public debate on homosexuality and homosexuals.